2018
DOI: 10.1002/dvdy.24617
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal development in the heterocercal caudal fin of spotted gar (lepisosteus oculatus) and other lepisosteiformes

Abstract: The present work highlights the power and importance of ontogenic studies and provides bases for future evolutionary and morphological investigations on actinopterygians fins. Developmental Dynamics 247:724-740, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…We also found that in more developed gar individuals, the plates of connective tissue had disappeared and were replaced by distal caudal radials except at the location of the hypural diastema (e.g., Fig. 7 in Desvignes et al, 2018). This result is consistent with the hypothesis that distal caudal radials develop from the fragmentation of the two plates of connective tissue, which are separated from each other at the hypural diastema.…”
Section: Hypural Diastema Complex Is Present In the Caudal Fin Of Botsupporting
confidence: 88%
See 2 more Smart Citations
“…We also found that in more developed gar individuals, the plates of connective tissue had disappeared and were replaced by distal caudal radials except at the location of the hypural diastema (e.g., Fig. 7 in Desvignes et al, 2018). This result is consistent with the hypothesis that distal caudal radials develop from the fragmentation of the two plates of connective tissue, which are separated from each other at the hypural diastema.…”
Section: Hypural Diastema Complex Is Present In the Caudal Fin Of Botsupporting
confidence: 88%
“…Although visible in those published works, authors did not mention or describe the hypural diastema, likely because, in contrast to adult teleosts, the hypural diastema is difficult to visualize in adult gars due to the weaker flexion of the notochord and the growth and shape of hypurals (Fig. 1F,G and Desvignes et al, 2018).…”
Section: Hypural Diastema Complex Is Present In the Caudal Fin Of Botmentioning
confidence: 98%
See 1 more Smart Citation
“…These larvae were killed in clove oil at 40 ppm, fixed in neutral‐buffered 4% paraformaldehyde for 12 hr, and rehydrated through a graded decreasing ethanol series (80, 50, and 25%). Specimens were cleared in 0.5% KOH (Merck, Darmstadt, Germany), and then double stained with Alcian Blue (8GX, Sigma‐Aldrich, Inc., St. Louis, MO) to reveal cartilages and stained with Alizarin Red (Alizarin Red S, Sigma‐Aldrich, Inc., St. Louis, MO) to reveal calcified bones . Cleared and stained larvae were stored in a solution of 70% glycerol (Merck, Darmstadt, Germany) and 0.3% KOH at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were cleared in 0.5% KOH (Merck, Darmstadt, Germany), and then double stained with Alcian Blue (8GX, Sigma-Aldrich, Inc., St. Louis, MO) to reveal cartilages and stained with Alizarin Red (Alizarin Red S, Sigma-Aldrich, Inc., St. Louis, MO) to reveal calcified bones. [106][107][108] Cleared and stained larvae were stored in a solution of 70% glycerol (Merck, Darmstadt, Germany) and 0.3% KOH at 4 C. Images were taken by a TrueChrome Metrics camera (TUCSEN, China) mounted on a compound microscope (GENUS, China). Images were processed with Corel Draw X6 software (Corel, Ottawa).…”
Section: Experiments V: Effect Of Cpas On Larval Morphology and Skelmentioning
confidence: 99%